Phytochemical Investigation and Biological Studies of Coffea benghalensis B. Heyne Ex Schult (Dhaka University Journal of Science, 2024)
The qualitative phytochemical screening of leaves and stems of Coffea benghalensis B. Heyne Ex Schult showed the presence of saponins, flavonoids, steroids, and cardiac glycoside. Stigmasterol, 1, 3- stearyl-oleyl-glyceride and stigmasterol glucoside were isolated and characterized from the dichloromethane extract of this plant leaves and stems by chromatographic and spectroscopic methods. Total caffeine content per hundred grams was estimated. Fatty acids were analyzed quantitatively by GLC. Total antioxidant capacity and antimicrobial activity of the plant leaves and stems extract were studied.Dhaka Univ. J. Sci. 72(1): 92-97, 2024 (January)